The sadness in the vision of adolescents: A dialogue with the field of emotional education (Revista Contexto & Educação, 2023)
The article is based on data collected for a research on Emotions at School that aimed to identify the elements that trigger different emotions and their impacts in educational terms, in the perception of adolescents.The present work is an excerpt from that investigation and seeks to analyze, from the perspective of Emotional Education, the events that cause the emergence of sadness, considering the theoretical assumptions of Arándiga and Tortosa (2003), Casassus (2009), Navas and Bozal (2012) and Bisquerra (2014), among others.This reserch adheres to the qualitative approach and was carried out through a semi-structured interview script, called the emoticons diary, with 526 students enrolled in elementar school II of basic education, who attend the 6th to 9th grade of the public school on the municipal school system. The results indicate that the emotion of sadness is recurrent in adolescents and is triggered by factors such as family conflicts, non-recognition by close people, loneliness, physical aggression, fear of death, family losses, school problems, bullying. The data shows to the family structure as essential in the process of emotional regulation, the adolescents' need to enjoy a safe environment and the well-being related to the feeling of protection offered by the parents. Keywords: Sadness; Emotional Education; School; Adolescents.
Keywords: Sadness; Emotional Education; School; Adolescents.